A ten-year review: Safety Culture and Safety Performance Studies in Malaysia - Arzahan, Intan Suraya Noor; Ismail, Zaliha; Yasin, Siti Munira; Nordin, Norraini; Idris, Nor Diana Mohd; Jusoh, Juereanor Mat; Arsad, Syahiza (CENTRAL ASIA AND THE CAUCASUS, 2022)
Safety culture or climate has been linked to safety performance in a growing number of studies. How safety and safety culture may enhance a company's safety performance has been the subject of several studies, particularly in high-risk sectors. Since safety culture is defined differently in different countries and organization in literature, it's important to have a look at some of the studies that have been conducted in the country, especially since the Malaysian OSHMP 2020 has highlighted the need for a preventive culture in every sector to promote a healthy work culture that benefits employees, employers, and the country. This ten-year review involved a database of Google Scholar to increase the likelihood of finding all related research in the country. Keywords such as "budaya keselamatan di Malaysia" (in Malay) and "Safety culture practice in Malaysia" were used to search the article. There are several criteria for choosing studies to evaluate, including (a) study in the subject of safety culture, (b), data gathered in Malaysia, and, finally, (c), papers from 2009-2019. The study design, types of industry involved, safety culture indicators selected, the influence of safety culture and safety performance in 10 research was reviewed by researchers in the current paper. Quantitative study design, mostly conducted in a high incident manufacturing setting, proactive safety culture measure is favored among researchers in safety culture. Four articles that studied the relationship with safety performance also showed a significant relationship with safety culture indicators. However, despite the importance of this subject, the number of studies is still low, especially when it comes to qualitative design. For OSHMP2025 to accomplish its goal of instilling preventative culture in all working environments, more study is needed to understand the relationship between the factors assessed, in a variety of different Malaysian sectors.